International Imaging Practices for Sacroiliac Joint MRI Acquisition Protocols in Patients with Juvenile Spondylarthritis - Arthur B. Meyers; Mirkamal Tolend; Walter P. Maksymowych; Rawan Hafiz; Tarimobo M. Otobo; Jacob L. Jaremko; Robert G. W. Lambert; Nele Herregods; Marion A. J. van Rossum; Jennifer Stimec; Simone Appenzeller; Shirley Tse; et al. (Journal of Clinical Medicine, 2026)
Background/Objective: International recommendations exist for MRI evaluation of sacroiliac joints (SIJs) in adult spondylarthritis (SpA) and other joints in juvenile (J)SpA. However, consensus recommendations for MRI acquisition protocols for SIJs in JSpA are lacking. Our survey gathered information on current imaging practices on SIJ MRI and expert opinions about imaging protocols. Methods: A survey was sent to an international group of pediatric radiologists and rheumatologists. Participants were asked about practices regarding sequences/planes, use of contrast, and preferred sequences/planes for evaluating individual lesions. Results: There were 38 unique survey respondents (North America, n = 19; South America, n = 1; Europe, n = 12; Asia, n = 2; Australia, n = 2; unknown = 2) from 32 institutions with a median of 15 (range 3–32) years of experience. Most (93%) institutions use the 2nd sacral vertebral body posterior cortex to plan coronal oblique sequences; most perform these as non-fat-suppressed T1W and fluid-sensitive sequences for evaluation of damage and inflammation, respectively. Among the 84% of institutions performing small field-of-view imaging, all include a coronal oblique plane, and 78% also do an axial oblique plane. Of all institutions, 22% utilize gradient echo (GRE) sequences. Most respondents (79%) did not consider contrast necessary for evaluating SIJs. Conclusions: Areas of agreement for a consensus MRI protocol for SIJ evaluation in JSpA include using a non-contrast-enhanced protocol and the S2 vertebral body posterior cortex to plan coronal oblique sequences. Further international consensus is required concerning the optimal scan plane to prescribe for axial sequences and the incorporation of an erosion-specific sequence into standard protocols.